Polymorphisms of organic cation transporter 1 and the drugs response - Dyah Aryani Perwitasari (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2011)
Polymorphisms of proteins which have an important role in drug transport, metabolism, and disposition in the bodycould affect the drugs efficacy and toxicity. The organic cation transporter 1 (OCT1), encoded by SLC22A1 gene,has been known as one of the polyspecific protein transporters which could affect some of the cationic drugresponse such as metformin, levodopa and imatinib. However, the findings of many studies an association of OCT1polymorphisms and drug response both in Caucasian and Asian were still inconsistent. Moreover, this study’s topicin Asians was still uncommon. This review was aimed to explore the polymorphisms of OCT 1 in Asians and Caucasiansand to find the challenges of the next studies in Asians. The articles about OCT1 polymorphisms were searched inthe PubMed with the keywords; OCT1 or SLC22A1, polymorphisms. There were ten articles of OCT1 polymorphismswhich are related to the drug response and most of the studies were performed in Caucasian subjects. In Caucasians,the rs622342 variant might associated with the response of metformin and levodopa. Moreover, the R61C and420del variants still showed the inconsistent findings associated with metformin response. The non-synonymousvariants which were found in Caucasians were not found in Asian. However, the new non-synonymous variantswere found in Japanese, Chinese, Indian and Korean population and some of them were associated with the metforminresponse. The recent findings found in Caucasians cancer patients, were related to the association of non-synonymousvariants haplotype and the 5-Hydroxytriptamine Receptor Antagonists drug response. The inconsistent results ofOCT1 polymorphisms studies could be related to the study’s sample size and design of the studies. Further studieswhich exploring the association of OCT1 polymorphisms and drug pharmacokinetic profiles and/or drug response,which were adjusted by genetic variants of proteins involved in drug tansport, metabolism and disposition are stillneeded in both Caucasians and Asians. Additional large studies also considering non-genetic risk factors are warranted,to implement the results of the various studies into clinical practice.Key words: OCT1- polymorphisms – Asians – Caucasians - drug response